Recent advances in understanding and managing chordomas: an update - Connors, Scott W. (F1000Res, 2020)
Chordomas are rare and difficult-to-treat tumors arising from the embryonic notochord. While surgery is the mainstay of treatment, and despite new techniques aimed at maximizing total tumoral resection, recurrence remains high and the probability of disease-free survival low. New breakthroughs in genetics, targeted molecular therapy, and heavy-particle beam therapy offer some promise as adjuvant treatments in addition to surgical resection. A multidisciplinary approach encompassing genetics, immunotherapy, radiation therapy, and surgery, at a facility experienced in the management of this complex disease, offers the best chance of survival and quality of life to patients while limiting the intrinsic morbidity of these treatments.